2015
DOI: 10.14814/phy2.12514
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiotensin II deteriorates left ventricular function with sympathoexcitation via brain angiotensin II receptor

Abstract: Sympathoexcitation contributes to the progression of heart failure. Activation of brain angiotensin II type 1 receptors (AT1R) causes central sympathoexcitation. Thus, we assessed the hypothesis that the increase in circulating angiotensin II comparable to that reported in heart failure model affects cardiac function through the central sympathoexcitation via activating AT1R in the brain. In Sprague-Dawley rats, the subcutaneous infusion of angiotensin II for 14 days increased the circulating angiotensin II le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
(160 reference statements)
0
8
1
Order By: Relevance
“…However, attention should be paid to the interaction between the sympathetic nervous system and the RAAS. Previous reports have revealed that circulating angiotensin II activated the sympathetic nervous system in part via brain angiotensin I type I receptors . We could not directly modulate the sympathetic nervous system and/or RAAS in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…However, attention should be paid to the interaction between the sympathetic nervous system and the RAAS. Previous reports have revealed that circulating angiotensin II activated the sympathetic nervous system in part via brain angiotensin I type I receptors . We could not directly modulate the sympathetic nervous system and/or RAAS in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…The sympatho-excitatory responses triggered by RAAS activation are mainly caused by the Ang-II through AT1 receptors in both periphery and central nervous system (CNS) (Braga et al, 2011). In the CNS, Ang-II effects involve the activation of AT1 receptors in the subfornical organ (SFO), with recruitment of the enzyme NADPH oxidase and ROS formation, especially superoxide anion (O 2 •– ), in the SFO, PVN, and RVLM (Griendling et al, 1994; Zimmerman et al, 2004; Braga et al, 2011; Shinohara et al, 2015). In addition to the already mentioned effects, Ang-II may also act as growth factor and as a stimulating agent of proinflammatory cytokines such as IL-6 and TNF-α (Kalra et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that central AT 1 R-induced oxidative stress causes sympathoexcitation in hypertension and heart failure. Moreover, baroreflex is found to have failed in hypertension and heart failure [ 5 , 6 , 7 , 17 , 18 ]. However, it has not been fully clarified whether the central AT 1 R-induced oxidative stress impaired baroreflex function or not.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nerve activities were presented as the normalized unit of the low frequency component (0.04–0.60 Hz) of the systolic arterial pressure variability [ 6 , 7 ]. Baroreflex sensitivity was measured using the spontaneous sequence method, as in our previous study [ 6 , 7 , 17 , 18 , 22 ].…”
Section: Methodsmentioning
confidence: 99%